Why do some countries get CSR sooner, and in greater quantity, than others? The political economy of corporate responsibility and the rise of market liberalism across the OECD: 1977-2007 - Daniel Kindermann (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2009)
How can we explain the historical and trans-national variation of Corporate Responsibility – business's voluntary engagement for social and environmental ends above legally mandated minimum standards – and how are we to understand this amorphous and essentially contested phenomenon? In this paper, I propose a political-economic explanation for the variation of Corporate Responsibility [Corporate Social Responsibility (CSR) and Corporate Citizenship]. I posit that Corporate Responsibility's temporal and cross-national variation is linked to its function of legitimating economic liberalization and market liberalism. Both employers and state officials have an interest in compensating for the hardships of liberalization and the weakening of institutionalized social solidarity. One way in which they seek to legitimate the market vis-à-vis their `stakeholders' and the electorate, and justify themselves vis-à-vis their own conscience, is through Corporate Responsibility. CR inoculates firms against burdensome regulation and justifies a light regulatory touch; it facilitates business-friendly institutional reforms; it helps to satisfy employers' needs and compensate for market failures and deficiencies in public provision. But CR cannot be understood in purely rational-instrumental let alone cynical terms. One of its most essential functions is to constitute businesspeople as responsible moral agents. Those in the engine rooms of contemporary capitalism – whether owners, managers, or employees – want to perceive themselves as serving the common good. This is true irrespective of capitalist `varieties.' In the place of Milton Friedman's assertion that the business of business is business, employers chant: `Free us up so we can do some Corporate Responsibility!' Using national Corporate Responsibility associations and their membership levels as a proxy for the institutionalization of CR, this paper develops and tests a political-economic explanation for the temporal and trans-national variation of CR. Using Corporate Responsibility associations, a novel proxy for the state of CR in a given country at a given time, I hypothesize that Liberal Market Economies tend to `get' CR earlier, and get more of it, than Social / Coordinated Market economies. Furthermore, Corporate Responsibility co-evolves with the decline of institutionalized social solidarity, `embedded liberalism' and `organized capitalism.' Empirical evidence from more than twenty OECD countries and from the CR `leader' United Kingdom and `laggard' Germany support these hypotheses and illustrate the co-evolution of CR and market liberalism during the past thirty years. In sum, this paper suggests that CR functions as a material and symbolic substitute for institutionalized forms of social solidarity. – – Wie können wir die transnationale Varianz von Corporate Responsibility – des freiwilligen Engagements von Unternehmen für soziale und ökologische Belange über gesetzlich vorgeschriebene Mindeststandards hinaus – erklären? Verbreitete sozialwissenschaftliche Erklärungen von Corporate Social Responsibility (CSR) und Corporate Citizenship stellen soziale Bewegungen und die Diffusion von sozialen Normen in den Vordergrund. Ich entwickele einen alternativen, polit-ökonomischen Ansatz: Corporate Responsibility trägt dazu bei, wirtschaftliche Liberalisierung und Marktliberalismus zu legitimieren. Sowohl Arbeitgeber als auch Politiker sind daran interessiert, die Härten der Liberalisierung und die Schwächung des institutionalisierten sozialen Zusammenhalts zu kompensieren. Corporate Responsibility ist ein Weg, das Vertrauen von Interessenvertretern und Wählern in den Markt zu stärken und gleichzeitig das eigene Gewissen zu entlasten; CR impft Unternehmen gegen zu starke Regulierung und ermöglicht doch einen zurückhaltenden Eingriff; es erleichtert unternehmensfreundliche institutionelle Reformen und es kann helfen, Marktversagen und Mängel in der Bereitstellung von öffentlichen Gütern zu kompensieren. CR darf jedoch nicht rein zweckrational, strategisch oder gar zynisch verstanden werden. Eines seiner wichtigsten Funktionen besteht darin, Geschäftsleuten ein Selbstverständnis als verantwortungsbewusste moralische Akteure zu ermöglichen. Alle Beteiligten im Räderwerk des zeitgenössischen Kapitalismus – ob Eigentümer, Führungskräfte oder Mitarbeiter – wollen sich als dem Gemeinwohl dienend verstehen, unabhängig von unterschiedlichen Spielarten des Kapitalismus. An Stelle von Milton Friedmans Behauptung ,the business of business is business' rufen Unternehmer, Wirtschafts-und Arbeitgeberverbände im Chor: ,Befreit uns von unseren Beschränkungen, damit wir uns in CR engagieren können! Mit der Hilfe eines neuen Indikators wird eine politisch-ökonomische Erklärung für die zeitliche und transnationale Varianz von CR entwickelt. Meine Hypothese ist, dass liberale Marktwirtschaften CR früher und in größeren Mengen ,bekommen' als soziale Marktwirtschaften. Darüber hinaus behaupte ich, dass der Anstieg von Corporate Responsibility einher geht mit dem Niedergang des institutionalisierten sozialen Zusammenhalts und des ,,organisierten Kapitalismus.“ Empirische Daten aus mehr als zwanzig OECD-Ländern und aus dem CRVorreiter England und dem ,,Nachzügler“ Deutschland unterstützen diese Thesen und veranschaulichen die Ko-Evolution des Aufstiegs von CR und der Liberalisierung der Wirtschaft in den letzten dreißig Jahren. Zusammengefasst, wird in diesem Papier vorgeschlagen, CR als materiellen und symbolischen Ersatz für institutionalisierte Formen des sozialen Zusammenhalts zu verstehen. Für Theorie und Forschungspraxis legen diese Ergebnisse nahe, politisch- ökonomische Institutionen und die Spielarten des Kapitalismus bei der Untersuchung von Corporate Social Responsibility (CSR) und Corporate Citizenship stärker in den Vordergrund zu rücken.
Keywords: 300; Corporate Social Responsibility; liberalization; market liberalism; quantity of CSR; timing of CSR; Varieties of Capitalism